ASTI Spatial Report **Feb 2012 Draft**. Arctic Species Trend Index 2011 Tracking trends in Arctic vertebrate populations through space and time. - Böhm, Monika; McRae, Louise; Deinet, Stefanie; Gill, Mike; Collen, Ben (CAFF International Secretariat, 2012)
Draft of the ASTI Spatial Report "Arctic Species Trend Index 2011. Tracking trends in Arctic vertebrate populations through space and time", submitted to the Arctic Council's Senior Arctic Officials meeting in Stockholm, Sweden, March 28-29 2012.